Examining the Social Organization Practices of Cybercriminals in the Netherlands Online and Offline - Leukfeldt, E. R. (International journal of offender therapy and comparative criminology, 2020)
This study focuses on the organization practices of networks of cybercriminals engaged in serious financial offenses, through a qualitative analysis of the Best and Luckenbill's sociological framework. The study utilized data collected regarding 18 separate criminals investigations from the Netherlands. The results demonstrate that the participants within these networks operated at various stages of deviant sophistication. Surprisingly, the majority of networks exhibit organizational sophistication based on their division of labor and extended duration over time. In fact, most of this sample could be classified as "teams" or "formal organizations." Furthermore, in contrast with prior studies, no loners were present and only a few networks could be classified as "colleagues" or "peers."